Antimicrobial Consumption among 66 Acute Care Hospitals in Catalonia: Impact of the COVID-19 Pandemic - Santiago Grau; Sergi Hernández; Daniel Echeverría-Esnal; Alexander Almendral; Ricard Ferrer; Enric Limón; Juan Pablo Horcajada; on behalf of the Catalan Infection Control Antimicrobial Stewardship Program (VINCat-PROA) (MDPI AG, 2021)
Background: Antimicrobials have been widely used during the COVID-19 pandemic. This study aimed to analyze the impact of the COVID-19 pandemic on the antimicrobial consumption of 66 hospitals in Catalonia. Methods: Adult antibacterial and antimycotic consumption was calculated as defined daily doses (DDD)/100 bed-days and DDD/100 discharges. Firstly, overall and ICU consumption in 2019 and 2020 were compared. Secondly, observed ICU 2020 consumptions were compared with non-COVID-19 2020 estimated consumptions (based on the trend from 2008-2019). Results: Overall, antibacterial consumption increased by 2.31% and 4.15% DDD/100 bed-days and DDD/100 discharges, respectively. Azithromycin (105.4% and 109.08% DDD/100 bed-days and DDD/100 discharges, respectively) and ceftriaxone (25.72% and 27.97% DDD/100 bed-days and DDD/100 discharges, respectively) mainly accounted for this finding. Likewise, antifungal consumption increased by 10.25% DDD/100 bed-days and 12.22% DDD/100 discharges, mainly due to echinocandins or amphotericin B. ICU antibacterial and antimycotic consumption decreased by 1.28% and 4.35% DDD/100 bed-days, respectively. On the contrary, antibacterial and antifungal use, expressed in DDD/100 discharges, increased by 23.42% and 19.58%. Azithromycin (275.09%), ceftriaxone (55.11%), cefepime (106.35%), vancomycin (29.81%), linezolid (31.28%), amphotericin B (87.98%), and voriconazole (96.17%) use changed the most. Observed consumption of amphotericin B, azithromycin, caspofungin, ceftriaxone, vancomycin, and voriconazole were higher than estimated values. Conclusions: The consumption indicators for most antimicrobials deviated from the expected trend pattern. A worrisome increase in antibacterial and antifungal consumption was observed in ICUs in Catalonia.